Biohydrogen Gas/Acetone-Butanol-Ethanol Production from Agave Guishe Juice as a Low-Cost Growing Medium - Alejandra G. Oliva-Rodríguez; Vianey de J. Cervantes-Güicho; Thelma K. Morales-Martínez; José A. Rodríguez-De la Garza; Miguel A. Medina-Morales; Silvia Y. Martínez-Amador; Ana G. Reyes; Leopoldo J. Ríos-González (Fermentation, 2023)
Different strategies have been assessed for the revalorization of guishe to obtain biomolecules. The juice obtained after the mechanical extraction of guishe is rich in phytochemicals and sugars which can be converted to other products. The objective of the present study was to evaluate the production of hydrogen and butanol at different guishe juice concentrations (and therefore, different sugar concentrations) via fermentation in batch mode using Clostridium acetobutylicum ATCC 824. Fermentation assays were performed in triplicate under anaerobic conditions at 35 °C for 142 h. Guishe juice was supplemented with all components of synthetic medium (salts, vitamins and reducing agents), except glucose, and diluted at different concentrations: 20%, 40%, 60%, 80% and 100%. For comparison purposes, a control was carried out in a synthetic medium using glucose as carbon source. Results showed a maximum butanol concentration of 5.39 g/L using 80% guishe juice, corresponding to a productivity and yield of 0.04 g/L h−1 and 0.24 g/g, respectively. Meanwhile, the highest productivity (1.16 L H2/L d−1; 1.99 mmol H2/L h−1) and yield (18.4 L/kg) of hydrogen were obtained with 40% guishe juice. This study demonstrates the potential of guishe juice to be used as a low-cost substrate for hydrogen and butanol production.